Design of an intelligent product that supports the task around health and safety in the home of the elderly - Artavia-Madrigal, Carolina (2019)
The project consists in the development of a functional prototype of an intelligent object to solve a present need in the costa rican reality, that improves the conditions of the elderly who do not live in the company of their relatives; specifically improving in the fulfillment of their basic tasks like: having an optimal and constant medication routine, counting with a viable alternative that allows to communicate their need for care or attention in cases of emergency, have an environment with healthy conditions to improve factors such as breathing, dryness and environmental health; and mobilize with good visibility in low light conditions.